Underwater vs conventional endoscopic mucosal resection in the management of colorectal polyps: a systematic review and meta-analysis - Kamal, Faisal; Khan, Muhammad Ali; Lee-Smith, Wade; Khan, Zubair; Sharma, Sachit; Tombazzi, Claudio; Ahmad, Dina; Ismail, Mohammad Kashif; Howden, Colin W.; Binmoeller, Kenneth F. (Endoscopy International Open, 2020)
Background Recently, underwater endoscopic mucosal resection (UEMR) has shown promising results in the management of colorectal polyps. Some studies have shown better outcomes compared to conventional endoscopic mucosal resection (EMR). We conducted this systematic review and meta-analysis to compare UEMR and EMR in the management of colorectal polyps. Methods We searched several databases from inception to November 2019 to identify studies comparing UEMR and EMR. Outcomes assessed included rates of en bloc resection, complete macroscopic resection, recurrent/residual polyps on follow-up colonoscopy, complete resection confirmed by histology and adverse events. Pooled risk ratios (RR) with 95 % confidence interval were calculated using a fixed effect model. Heterogeneity was assessed by I2 statistic. Funnel plots and Egger’s test were used to assess publication bias. We used the Newcastle-Ottawa scale (NOS) for assessment of quality of observational studies, and the Cochrane tool for assessing risk of bias for RCTsResults Seven studies with 1291 patients were included; two were randomized controlled trials and five were observational. UEMR demonstrated statistically significantly better efficacy in rates of en bloc resection, pooled RR 1.16 (1.08, 1.26), complete macroscopic resection, pooled RR 1.28 (1.18, 1.39), recurrent/residual polyps; pooled RR 0.26 (0.12, 0.56) and complete resection confirmed by histology; pooled RR 0.75 (0.57, 0.98). There was no significant difference in adverse events (AEs); pooled RR 0.68 (0.44, 1.05). Conclusions This meta-analysis found statistically significantly better rates of en bloc resection, complete macroscopic resection, and lower risk of recurrent/residual polyps with UEMR compared to EMR. We found no significant difference in AEs between the two techniques.